Loneliness and social anxiety predicting smartphone addiction among undergraduates in a Malaysian public university - Jun, Lim Yan; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Mohamed Yusop, Yusni (Human Resources Management Academic Research Society (HRMARS), 2023)
The youth population comprises individuals who are highly adaptable in general to the use of smartphones on a daily basis for various purposes. However, excessive use of the digital communication tool has caused physical and emotional distress in their daily habits. The main purpose of this study was to determine the relationship between loneliness and smartphone addiction among undergraduates at a Malaysian public university. A total of 318 undergraduates participated in this study, selected via random sampling. Data was collected through a set of self-administered online questionnaire: UCLA-Loneliness Scale-Version 3 was used to measure loneliness; and Smartphone Addiction Scale Short Version was used to measure smartphone addiction. Findings demonstrate a positive correlation between loneliness and smartphone addiction, suggesting that social interaction is vital in preventing problematic or addictive behaviour among undergraduates. The implications of this study for university counsellors, lecturers and management were highlighted to strategise intervention plans to avoid addictive behaviours and promote a healthy mental health state among the students. Recommendations for future research were discussed to expand its focus to various public universities in Malaysia and explore the predictive factors for undergraduates’ smartphone addiction.